A primer on the mouse basal body. Issue 1 (December 2016) - Garcia, Galo; Reiter, Jeremy
Abstract The basal body is a highly organized structure essential for the formation of cilia. Basal bodies dock to a cellular membrane through their distal appendages (also known as transition fibers) and provide the foundation on which the microtubules of the ciliary axoneme are built. Consequently, basal body position and orientation dictates the position and orientation of its cilium. The heart of the basal body is the mother centriole, the older of the two centrioles inherited during mitosis and which is comprised of nine triplet microtubules arranged in a cylinder. Like all ciliated organisms, mice possess basal bodies, and studies of mouse basal body structure have made diverse important contributions to the understanding of how basal body structure impacts the function of cilia. The appendages and associated structures of mouse basal bodies can differ in their architecture from those of other organisms, and even between murine cell types. For example, basal bodies of immotile primary cilia are connected to daughter centrioles, whereas those of motile multiciliated cells are not. The last few years have seen the identification of many components of the basal body, and the mouse will continue to be an extremely valuable system for genetically defining their functions.